Consideration of the effect of self-aggregation in nanoscale CdS clusters - Assilbekova, A.M.; Aldongarov, A.A.; Irgibaeva, I.S. (Recent Contributions to Physics, 2021)
Quantum dots, such as cadmium sulfide (CdS), are semiconductor nanocrystals that possess unique optical properties, including wide-range excitation, size-tunable narrow emission spectra and high photostability. The size and composition of quantum dots can be varied to obtain the desired emission properties and make them suitable for various optical and biomedical applications. In this article, the effect of self-aggregation on the electronic absorption spectra and on the dipole moment in CdS nanoparticles is considered using computer modeling methods based on the density functional tight-binding (DFTB). The object of the study is four CdS structures and two models of an aggregated dimer for each cluster. The construction of dimers of cadmium sulfide clusters showed that a higher level of passivation can be achieved in comparison with the initial monomers. In this case, the construction of dimers should occur along the direction of the dipole moment of the monomer in order to minimize it. Therefore, it can be assumed that the dipole moment plays a key role in the formation of trap states in nanosized clusters of cadmium sulfide, and the problem of passivation is reduced to minimizing the dipole moment.